Pension plans assumptions: the case of discount rate. Issue 1 (7th May 2019) - Morais, Ana Isabel; Pinto, Inês
Abstract : Purpose: In 2009, the International Accounting Standards Board started revising International Accounting Standard (IAS) 19 to improve the requirements for managing the annual expense of a pension plan. The revised standard became effective in 2013. The purpose of this paper is to investigate what effect this revision had on managerial discretion. The paper also examines the implications of the revision on the value relevance of accounting information. Design/methodology/approach: The authors use a sample of 72 firms listed on the FTSE 100 that have defined benefit plans for the period between 2009 and 2015. The authors use a regression discontinuity design to analyse the effect from the revision of IAS 19 on the choice of managers regarding the expected rate of return-on-plan assets. The paper also investigates whether firms with higher pension sensitivity are more likely to manage earnings upward before the revision of IAS 19. Further, the paper studies the value relevance of earnings after the revision of the accounting standard. Findings: Consistent with predictions, the results show that the adoption of the revised IAS 19 limits the use of the expected rate of return on assets to manage the annual expense of defined benefit plans. This finding shows a sharp increase in the value relevance of earnings. Practical implications: This finding is useful for users and preparers of financial statements and regulatory bodies as it identifies not only the influence of a change in the accounting standard for earnings management but also provides evidence on the consequences of managers' discretion. Originality/value: This paper provides direct evidence on the relationship between regulation and financial reporting discretion. It also provides evidence to accounting standard setters that the revision of IAS 19 improves the value relevance of financial information, which gives additional justification to the changes introduced by regulators.